Identification of the kinanthraquinone biosynthetic gene cluster by expression of an atypical response regulator. Issue 3 (3rd February 2021) - Takao, Risa; Sakai, Katsuyuki; Koshino, Hiroyuki; Osada, Hiroyuki; Takahashi, Shunji
ABSTRACT: Recent advances in genome sequencing have revealed a variety of secondary metabolite biosynthetic gene clusters in actinomycetes. Understanding the biosynthetic mechanism controlling secondary metabolite production is important for utilizing these gene clusters. In this study, we focused on the kinanthraquinone biosynthetic gene cluster, which has not been identified yet in Streptomyces sp. SN-593. Based on chemical structure, 5 type II polyketide synthase gene clusters were listed from the genome sequence of Streptomyces sp. SN-593. Among them, a candidate gene cluster was selected by comparing the gene organization with grincamycin, which is synthesized through an intermediate similar to kinanthraquinone. We initially utilized a BAC library for subcloning the kiq gene cluster, performed heterologous expression in Streptomyces lividans TK23, and identified the production of kinanthraquinone and kinanthraquinone B. We also found that heterologous expression of kiqA, which belongs to the DNA-binding response regulator OmpR family, dramatically enhanced the production of kinanthraquinones. Graphical Abstract: